GMAT Club

Kudos owned by the user


Bunuel received 9 Kudos for post Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =.

GiverPostDate
GCRJRe: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =01-Nov-2022
closertotop10Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =22-Jun-2022
aman.bhardwaj3Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =04-Dec-2021
Liberatehk1920Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =20-Dec-2020
montanhaf100Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =08-Apr-2020
DiwabagRe: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =06-Jul-2019
jendenyesRe: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =09-Nov-2017
shinrai15Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =10-Sep-2017
RalphcuisakRe: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =17-Jan-2015

Page 1 of 1